Seminal vesicle sperm aspiration in the diagnosis of ejaculatory duct obstruction - Orhan, I; Onur, R; Çayan, S; Koksal, IT; Kadioglu, A (Blackwell Science Ltd, 1999)
Objective To determine the effectiveness of seminal vesicle aspiration in the diagnosis and treatment of patients with ejaculatory duct obstruction. Patients, subjects and methods Between March 1998 and February 1999, 10 infertile men with ejaculatory duct obstruction (EDO, mean age 32.7 years, range 25-47) and 10 fertile volunteers (mean age 33.2 years, range 25-42) underwent transrectal ultrasonography (TRUS) and TRUS-guided seminal vesicle aspiration. The volume of and presence of motile sperm in the aspirate was compared with the TRUS findings for both groups. Results From TRUS of the patients with EDO, the mean (sd, range) transverse diameter of the right and left seminal vesicles were 1.97 (0.54, 0.8-2.6) cm and 1.93 (0.53, 0.9-2.6) cm; the corresponding values in the control group were 1.03 (0.15, 0.8-1.3) cm and 1.0 (0.12, 0.8-1.4) cm, respectively (P < 0.001). In all, 20 aspirate samples were obtained from the patients with EDO by bilateral seminal vesicle aspiration and only one (10%) had no sperm within the aspirate fluid. Of these 10 patients, two had immotile sperm and the remaining seven (14 samples) had a mean motile sperm count of 0.63 (0.45, 0.1-1.0)x10(6) /mL, whereas seven of eight men assessed in the control group had no motile sperm (one patient had immotile sperm within the aspirate fluid); this difference was significant (P < 0.01). Conclusions The aspiration of significant numbers of motile sperm from the seminal vesicles suggests the presence of distal obstructions of the ejaculatory duct and enables infertile couples to be candidates for assisted reproduction. However, there is a need for further research to determine the use of this technique in the diagnosis of partial EDO.
Keywords: ejaculatory duct; obstruction; seminal vesicle; aspiration